Contextual dimensions and policy actors of food and nutrition education - Souza, Júlia Graciela de; Heinzle, Marcia Regina Selpa (Education Policy Analysis Archives, 2019)
According to Ball, Maguire and Braun (2016), the performance of politics in an institution depends on several factors, including contextual dimensions: situated contexts, professional cultures, material contexts and external contexts. These contexts impact how a policy will be interpreted, translated, and put into action. In view of this theoretical framework, we seek to understand the contextual dimensions that influence the performance of the Food and Nutrition Education (EAN) in a nutrition course of a university of Southern Brazil. A documentary analysis of the pedagogical project of course and semi-structured interview generated the data that was analyzed using the discursive textual analysis. The results reveal that the four contextual dimensions investigated influence the performance of the policy. Although the policy will suffer from the constraints of situated context, material contexts and external contexts, the performance of EAN policy depends on the roles assumed by policy actors who seek through an integrated curriculum and alternatives drawn to put EAN policy on the scene.